Can age‐related changes in parental care modulate inbreeding depression? A test using the burying beetle, Nicrophorus orbicollis. Issue 10 (5th October 2022) - Schrader, Matthew; Hughes, Parker; Jenkins, Samuel; Kusher, Ian; Lopez, Jonathan; Oglesby, Harriet; McGhee, Katie E.
Abstract: Parental care has been shown to reduce the magnitude of inbreeding depression in some species with facultative care. However, parents often vary in the quality or amount of care they provide to their offspring, and it is less clear whether this variation also impacts the magnitude of inbreeding depression. Here, we tested whether age‐related changes in parental care modulate the expression of inbreeding depression in the burying beetle, Nicrophorus orbicollis . Consistent with previous studies, we found that older parents produced larger broods of offspring than younger parents without sacrificing mean larval mass. Inbreeding depression was evident in several fitness‐related traits: brood size at dispersal, the proportion of the brood that survived to eclosion, and mean age at death were all reduced in inbred broods compared with outbred broods. Surprisingly, inbred offspring were heavier at dispersal than outbred offspring. This was likely due to reduced sibling competition in inbred broods. Despite evidence for age‐related changes in parental investment and the existence of inbreeding depression, there was no evidence that an interaction between the two influenced any of the traits we measured. Our results suggest that age‐related changes in parental care may be too slight to influence the expression of inbreeding depression. Abstract : Here, we tested whether age related changes in parental care modulate the expression of inbreeding depression in the burying beetle, Nicrophorus orbicollis . Despite evidence for age related changes in parental investment and the existence of inbreeding depression, there was no evidence that an interaction between the two influenced any of the traits we measured. Our results suggest that age‐related changes in parental care may be too slight to influence the expression of inbreeding depression.